Impact of Physical Mobility, Decision Making and Economic Empowerment on Gender-Based Violence Among Married Women in Rural Himachal Pradesh - Singh, Sanjeet; Kumar, Sanjeev (Stallion Journal for Multidisciplinary Associated Research Studies, 2025)
Gender-based violence (GBV) remains one of the most pervasive human rights violations in the world, affecting the lives of women at an alarming rate. This paper investigates the association of physical mobility, decision-making power, and economic resources with GBV among married women in Bhoranj Block, Hamirpur District, Himachal Pradesh. A cross-sectional study was carried out with a total of 110 respondents comprising 50 married men and 60 married women aged 18-25 years. Data were obtained through structured interviews measuring experience of physical and sexual violence, women's empowerment indicators, and socio-economic factors. The association between empowerment indicators and GBV was assessed using descriptive statistics, chi-square tests, and logistic regression models. 16.3% and 21.5% of respondents reported physical and sexual violence, respectively. Restricted mobility among women was associated with higher odds of violence (AOR=1.41 for physical violence, AOR=0.45 for sexual violence). When men had little or no say in decisions, the odds of GBV risk were considerably greater (AOR=2.23, 95% CI: 1.12-4.76 for physical violence; AOR=1.89, 95% CI: 1.04-3.91 for sexual violence). Economic dependence proved to be a key predictor for both types of violence, with financially dependent women experiencing 2.45 times higher odds of physical violence and substantially higher risk of sexual violence (AOR=0.22, p < 0.001). Both spousal controlling behavior and alcohol consumption, as well as greater age gaps, were also strongly linked to heightened risk of GBV. The results underscore the protective effect of women's empowerment against GBV. Policies that ensure empowerment through economic independence, mobility, and decision-making power, along with community programs and legal literacy initiatives, should form the foundation to tackle GBV in rural Himachal Pradesh. This requires targeted work to counter patriarchal norms, control alcohol consumption, and offer support services for victims.